How should unconventional oil and gas be regulated? The role of natural resource dependence and economic insecurity. (January 2019) - Mayer, Adam; Malin, Stephanie
Abstract: The U.S. is undergoing a rapid energy transition, driven in large part an explosion in oil and gas production driven by unconventional drilling technologies. Some communities have embraced the boom in new oil and gas production, often resisting efforts to regulate the oil and gas industry. On the other hand, some states and municipalities have effectively banned new oil and gas drilling. In this paper, we examine how natural resource dependence, local economic conditions, and perceived economic benefits relate to support for restrictive oil and gas regulations in Colorado, US. Using representative survey data, our results suggest that perceived benefits, especially in the form of tax revenue, predict oil and gas policy preferences, while local and personal economic circumstances have little impact. Highlights: Communities around the world host oil and gas development. Natural resource dependent communities often resist efforts to regulate the oil and gas industry. Our results suggest that economic conditions do not explain all oil and gas regulatory preferences. Residents who perceive significant economic benefits still support some modest regulations.